Coordenação das transações de cana-de-açúcar das usinas sucroalcooleiras no oeste paulista: complementos contratuais e pluralidade - Feltre, Cristiane (2013)
In the activity of supplying sugar cane to the mills in Brazil, there are governance structures differentiated between plants and also for the same plant. These structures range from the highest level of hierarchy vertical integration, in which the plant produces its own fields in the raw material for its supply to the less of hierarchy spot market, in which the plant gets the sugar cane from outside farmers without contracts or commitments with the following crops. Between these two extreme governance structures have been identified other supply arrangements called hybrids. The main objective of this thesis is to identify the factors that influence the choice of governance structures present in the supply of sugar cane in a given group of mills in the West region of São Paulo/BR State. The specific objectives are to: a) show what determines the representativeness of each governance structure in the mills selected in the West region of the state of São Paulo; b) identify the existence of plural forms; c) analyze the factors that justify the option in the mills for plural or singular forms of governance in the same type of transaction in the region West of the state of São Paulo; and d) compare the supply strategies of the plants of western São Paulo. This analysis was performed under the focus of the New Institutional Economics literature, especially dealing with the characteristics of transactions Transaction Cost Economics. The research is characterized, as the social group as explanatory research. To this end, it was applied an interview to the decision makers for supplying of raw material in the mills that represent a group of ten unities located in the west of São Paulo by competing for suppliers and land . It was observed that the characteristics of the transactions locational and temporal specificity, uncertainty and frequency are not determinative for the choice of governance structures, as recommended by the literature of transaction costs. These same characteristics make plants adopt formal mechanisms, provided for in contracts, and informal control transactions. The characteristics of transactions in supply of sugarcane exclude one of the governance structures observed in the literature the spot market but do not determine the uniqueness of others. The results also indicate that the plurality of transactions that serve the same purpose is common in the units studied and is related to the history of these plants, the need to eliminate some uncertainty in the supply and the balance between risks and disadvantages of singular forms. The singular forms, observed in only one case, appeared only as a function of need for financial restructuring of the company. Finally, it was noted that there is a significant diversity of arrangements for the supply of sugarcane in western São Paulo, hampering the framework of the structures observed in this research that was presented in the literature so far.